What is Fiction? Theorising 'Fictional Narrativisation' (KULT_online, 2011)
Germanist J. Alexander Bareis published his doctoral thesis on Fiktionales Erzählen (Fictional narrativisation: On the theory of literary fiction as make-believe) at the University of Gothenburg in 2008. His aim is to develop an integrative theory of specifically literary methods of 'fictional narrativisation'. This theory is founded on combining the transmedial theory of fiction by the American philosopher Kendall L. Walton with narratological concepts that are central to any analysis of fictional narratives. Although the theory of 'fictional narrativisation' falls short of its aim, Bareis' thesis is worthwhile reading for its insights into the central concerns and aporia of theories of fiction. Moreover, it provides a very good introduction to Walton's transmedial approach to theorising fiction.